Q: How do you solve 6 plus m equals 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-6

(x-3)(x-2)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

a= -0.8

2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3

Related questions

minus 5

6+z = 3 z = 3-6 z = -3

-6

(x-3)(x-2)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

25-7=18 18/3=6

No! It equals 15, but 9-6=3.

a= -0.8

you cannot solve this without more information. When 3 variables are involved, you need 2 equations to solve for the answers for both variables.

2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3

No.

It works out that x = 6 and y = 3 or as (6, 3)